Assessment of risk factors for surgical complications in neonatal circumcision clinic - Kim, Jin K.; Koyle, Martin A.; Chua, Michael E.; Ming, Jessica M.; Lee, Min Joon; Kesavan, Amre; Saunders, Megan; Dos Santos, Joana (Canadian Urological Association Journal, 2018)
Introduction: Despite the widespread use of circumcision, there is little understanding regarding risk factors associated with its complications. This investigation assesses potential risk factors contributing to complications of circumcision. Methods: A retrospective review of all males who underwent a neonatal circumcision in our institution’s pediatric urology clinic between January 2015 and June 2017 was performed. Continuous variables were dichotomized to determine a clinically relevant cutoff value. Multivariate regression analyses were used to identify risk factors for primary outcomes (early/late complications) and secondary outcomes (emergency room [ER] visitation, return to operating room, post-circumcision communications). Results: A total of 277 patients were identified. The mean age and weight were 28.4 days and 4.3 kg, respectively; 93.1% of cases were elective and 12.3% of patients had comorbidities. Circumcisions were performed using Mogen (61.4%) or Gomco clamps (39.6%) under local anesthesia. Overall, 35 patients experienced complications (12.6%). There were 18 patients (6.5%) with bleeding requiring sutures at time of circumcision. Twenty-six patients (9.4%) experienced long-term complications, with penile adhesions being the majority (84.6%). One (0.4%) of these patients had a Clavien-Dindo 3 complication requiring surgery for a skin bridge that could not be separated. One patient (0.4%) visited the ER due to postoperative bleeding from the circumcised area, which was managed conservatively. Multivariate regression analysis identified weight >5.1 kg as a risk factor for bleeding requiring sutures (odds ratio [OR] 4.145; 95% confidence interval [CI] 1.246–13.799) and long-term complications (OR 3.738; 95% CI 1.356–10.306). No risk factors were identified for other outcomes (return to operating room, ER visitation, postcircumcision email/telephone communications). Conclusions: This investigation of neonatal circumcision revealed that patients weighing >5.1 kg may be at higher risk of bleeding and long-term complications, such as adhesions.